Serological, phenotypic and molecular characterization of brucellosis in small ruminants in northern Algeria - Nabi, Ibrahim; Achek, Rachid; Karim, Abdelkadir; Melzer, Falk; Brangsch, Hanka; Elschner, Mandy C.; Neubauer, Heinrich; El-Adawy, Hosny (Frontiers in Microbiology, 2025)
Brucellosis is considered a common bacterial zoonotic disease of high prevalence in countries of the Middle East and the Mediterranean region with economic and public health impact. The present study aimed to investigate the current situation of brucellosis in small ruminants reared in Médéa and Sidi Bel-Abbès provinces, north Algeria. To achieve this objective, 96 sera (77 sheep and 19 goat) and 57 milk (42 sheep and 15 goat) samples were collected from suspected infected animals and serologically analyzed by using ELISA. For isolation of Brucella spp., four placentas, two fetuses and forty-four milk samples were subjected to microbiological investigation. Whole genome sequencing (WGS) was used for genomic analysis of isolated Brucella species. The results of this study showed that anti-Brucella antibodies were detected in 46 (83.6%) and 52 (54.2%) milk and serum samples, respectively. However, among 27 cases where blood samples were negative, anti-Brucella antibodies were still detected in 19 of the corresponding milk samples, resulting in an overall discordance rate of 36.5%. Ten Brucella melitensis were isolated and identified from six sheep and four goats. Of these, eight originated from milk samples. The isolated strains were assigned to sequence type ST-11 using Multilocus sequence typing (MLST). Five isolates revealing high similarity (0–2 nucleotide differences) originated from different farms, indicating a close transmission link. However, two identical caprine isolates and three other isolates showed notable genotypic variation, in comparison. The highest base difference (449–462 nucleotides) was observed for an ovine isolate originating from Sidi Bel-Abbès. The phylogenetic analysis and clustering with the West Mediterranean lineage of B. melitensis revealed high genetic similarity of the investigated isolates with B. melitensis of human origin from North Africa and travel-associated ‘European’ cases, especially from Morroco, Tunisia, Sweden and Italy. The results of this study highlight brucellosis in small ruminants as a significant public health risk and will help to develop effective control strategies in Algeria. These findings provide specific evidence of this risk, with Brucella isolation from milk and by linking theses isolates to human cases in Algeria and abroad. The use of WGS-based analysis has revealed effective in tracing patterns of transmission, and can be recommended for tracking outbreaks at a high resolution.